Genome-Wide Analysis of Differentially Expressed Genes During the Early Stages of Tomato Infection by a Potyvirus - Alfenas-Zerbini, Poliane; Maia, Ivan de Godoy [UNESP]; Favaro, Regiane D. [UNESP]; Cascardo, Julio C. M.; Brommonschenkel, Sergio H.; Zerbini, Francisco Murilo (Amer Phytopathological Soc, 2009)
Plant responses against pathogens cause up-and downward shifts in gene expression. To identify differentially expressed genes in a plant-virus interaction, susceptible tomato plants were inoculated with the potyvirus Pepper yellow mosaic virus (PepYMV) and a subtractive library was constructed from inoculated leaves at 72 h after inoculation. Several genes were identified as upregulated, including genes involved in plant defense responses (e. g., pathogenesis-related protein 5), regulation of the cell cycle (e. g., cytokinin-repressed proteins), signal transduction (e. g., CAX-interacting protein 4, SNF1 kinase), transcriptional regulators (e. g., WRKY and SCARECROW transcription factors), stress response proteins (e. g., Hsp90, DNA-J, 20S proteasome alpha subunit B, translationally controlled tumor protein), ubiquitins (e. g., polyubiquitin, ubiquitin activating enzyme 2), among others. Downregulated genes were also identified, which likewise display identity with genes involved in several metabolic pathways. Differential expression of selected genes was validated by macroarray analysis and quantitative real-time polymerase chain reaction. The possible roles played by some of these genes in the viral infection cycle are discussed.